Mechanical behavior of plaster reinforced with abaca fibers. (30th November 2015) - Iucolano, Fabio; Caputo, Domenico; Leboffe, Flavio; Liguori, Barbara
Graphical abstract: Highlights: The addition of abaca fibers didn't involve any delay on the plaster setting time. Abaca fibers treated with distilled water showed a better adhesion with gypsum matrix. An addition of 2 wt.% of abaca fibers leads to an enhanced toughness of the composites. Abstract: In the last decades, eco-friendly materials are playing an increasingly important role in the building industry. Particularly, many studies deal with the use of natural fibers as replacement to synthetic fibers in reinforced composites. Natural fibers are already employed in many building materials, due to their attractive features, such as good mechanical properties, low cost, low density, low thermal conductibility and recyclability. In this research, the interaction between abaca fibers and gypsum matrix was studied, in order to produce fiber-reinforced plasterboards with enhanced toughness performances. Firstly, the influence of some parameters (i.e. fibers dimensions, amount of fiber addition, water to gypsum ratio) on physical and mechanical behavior of the plasters was evaluated. In order to improve the composite performances, the fibers were subjected to different chemical treatments (with distilled water, NaOH solution and EDTA solution) to modify the surface characteristics and to improve the adhesion with the gypsum matrix. Their effects were explored by scanning electron microscope and mechanical tests, such as pull-out and flexural strength tests. The treatments with NaOH and EDTA solutions resulted in a worsening of the mechanical behavior of the composites, while the fibers treated with distilled water gave a better adhesion with the inorganic matrix.